The correlation between students’ mastery of simple past tense and their ability in writing recount text - Lestari; Fitri Novia; Rachmanita (Relawan Jurnal Indonesia, 2021)
The goal of this study determined a relationship between students' knowledge of the simple past tense and their ability to create a recount text in tenth-grade pupils of SMA N 07 Ogan Ilir. The study's participants were all Tenth-Grade Students at SMA N 07 Ogan Ilir. A total of 86 students were present in the population. The sample consisted of 86 students who were chosen using a total sampling technique. This investigation was carried out using correlation research. The data was administered through simple past tense mastery test and writing recount text. Pearson Product Moment correlation was employed to analyze the data.The correlation coefficient, or r-obtained (0.325), was found higher than r-table (0.176), with a p-value of 0.0020.05. It meant that learners' grasp of the simple past tense and their ability to write recount texts were related. It is possible to conclude that students' knowledge of the simple past tense has a significant impact on their ability to write recount material.